AWS Certified Security Study Guide : Specialty (SCS-C01) Exam /: Specialty (SCS-C01) Exam. (2020) - Neto, Marcello Zillo; Santana, Gustavo A. A; Sapata, Fernando; Munoz, Mauricio; Moraes, Alexandre M. S. P; Morais, Thiago; Goldfarb, Dario Lucas
No abstract available